TACKLING INDONESIA'S PLASTIC WASTE CRISIS: A POLITICAL PERSPECTIVES AND POLICY IMPLICATIONS - Komarudin, Ujang; Ayuningtyas, Dinda (JURNAL TRIAS POLITIKA, 2024)
Abstrack : The escalating plastic waste crisis in Indonesia, fueled by population growth and widespread plastic usage, presents a critical environmental challenge. This study examines the Indonesian government's response to this crisis through a political lens, aiming to uncover the policy implications of its initiatives. Employing qualitative methods and an extensive literature review, this research delves into the government's strategies. Using the theory of national interest, the study focuses on policy implementation, diplomatic efforts, and public participation to set ambitious targets for waste reduction, aiming for a 30 percent decrease in overall waste by 2025. To achieve these objectives, the government has enacted various regulations and measures aimed at curbing plastic pollution. Furthermore, Indonesia has engaged in diplomatic endeavors, collaborating with international partners and participating in multilateral forums to address plastic pollution regionally and globally. Moreover, the study underscores the importance of public participation in mitigating the plastic waste crisis. It assesses the effectiveness of collaborative efforts in combating plastic pollution. Through an in-depth analysis of these factors, this study offers valuable insights into Indonesia's response to the plastic waste crisis, with the aim of informing future policymaking and facilitating effective strategies for plastic waste reduction in the country.